Study on the Effect of Delayed Field Compaction Duration on the Properties of Subgrade Soil in Road Construction - هارون إدريس أبوشيبه; عبد الباسط عبد الرحمن; محمد النعيري; عبد المطلب بن سليم (African Journal of Advanced Pure and Applied Sciences, 2026)
This study discusses the evaluation of the physical and mechanical changes occurring in the unbound granular base layer due to prolonged exposure to weathering and traffic loading prior to the final compaction and asphalt covering. The research adopted a comparative methodology encompassing three main phases. It began with the characterization of the source material and verification of its compliance with standard specifications (ASTM D422, AASHTO T180) in terms of particle size distribution and mechanical properties. In the second phase, a notable deterioration in the soil’s structural framework was observed after one year of being laid bare, where storm water runoff and vehicle movements caused the particle size distribution to deviate from the allowable design limits, accompanied by a tangible increase in the percentage of fine particles and loss of layer stability. In its third phase, the study moved to the practical side by treating the deteriorated soil and re-adjusting its gradation instead of fully replacing it. The results showed that the process of "gradation adjustment" by adding precise proportions of sand and coarse aggregate (1% sand, 1.5% coarse aggregate of size 20–30 mm, and 1% aggregate of size 0–5 mm) succeeded in bringing the gradation curve back within the specification limits. The study concluded that leaving base layers exposed leads to substantial changes in their properties, necessitating engineering re-adjustment. It recommended conducting periodic verification tests and adopting localized addition techniques as an economical and sustainable solution for restoring the design efficiency of the road.